A CRITIQUE OF MAX MULLER'S METHODOLOGY OF MYTHOLOGY - Brockway, R. W. (Journal of Dharma, 1977)
Max Miiller's Essay in Comparative Mythology (1856) was the earliest significant discussion of comparative religion, and, it could be said that Miiller was the father of Religionswissenschaft or ReligiousStudies. At any rate, he coined the term. Muller ap- proached the study of religion from his knowledge of Sanskrit and other ancient languages. He was primarily a philologist and his methodology was linguistic. Interested in archaic forms of re- ligion, he suggested that contemporary primitives might preserve some very ancient mythologies, rituals, and beliefs which could be taken as survivals from prehistoric times, and that from them one could discern originals. Miiller pioneered this particular approach. He considered the currently popular fetishism theory to be an example of the grossly inadequate notions of the theorists like Comte who had nothing but conjecture and that data was wilfully distorted. What was even more serious, in Muller's view, was the poverty of information about primitives, the unreliability of the reports, and the superficiality of the reporters. Muller did not think it possible to go behind the facade of contemporary primitivism to the primaeval and consequently, discarded the anthropological approach.